A Pilot Study on Parameter Setting of VisiTag™ Module during Pulmonary Vein Isolation - Yu-Chuan Wang; Bo Huang; Kang Li; Peng-Kang He; Er-Dong Chen; Yu-Long Xia; Jie Jiang; Qin-Hui Sheng; Jing Zhou; Yan-Sheng Ding (Cardiology Research and Practice)
Objectives. To identify optimal predefined criteria (OPC) for filters of the VisiTag™ module in the CARTO 3 system during pulmonary vein isolation (PVI). Methods. Thirty patients with atrial fibrillation (AF) who experienced PVI first were enrolled. PVI was accomplished by using a Thermocool SmartTouch catheter. Ablation lesions were tagged automatically as soon as predefined criteria of the VisiTag™ module were met. OPC should be that ablation with the setting resulting in the conduction gap (CG) as few as possible, while contiguous encircling ablation line (CEAL) without the tag gap (TG) on the 3D anatomic model as much as possible. Result(s). When ablation with parameter setting is being catheter movement with a 3 mm distance limit for at least 20 s and force over time (FOT) being off, there were 60 CEAL without TG on the 3D anatomic model. However, 26 CGs were found. After changing FOT setting to be a minimal force of 5 g with 50% stability time, 22 TGs were displayed. Of them, 20 TGs were accompanied by CGs. On reablation at sites of TG with changed parameter setting, 18 CGs were eliminated when 20 TGs disappeared. When reablation with FOT is being a minimal force of 10 g with 50% stability time, 6 remaining CGs were eliminated. However, there was no CEAL. With a mean of follow-up 10.93 months, 2 patients with persistent AF suffered AF recurrence. Conclusion. A 3 mm distance limit for at least 20 s and FOT being a minimal force of 5 g with 50% stability time might be OPC for the VisiTag™ module.